Co-culture with Lactobacillus plantarum SC-1 facilitates ergosterol synthesis in Monascus purpureus through MpSet1-affected H3K4ac establishment - Wu, Zhongling; Liu, Zhenmin (Frontiers in Microbiology, 2025)
IntroductionIn fungi, ergosterol synthesis is regulated by multiple transcription factors such as Upc2, but the regulation of ergosterol synthesis in Monascus remains unclear.MethodsWe performed a co-culture system of Monascus purpureus (M. purpureus) with Lactobacillus plantarum SC-1 strain isolated from sauerkraut to detect ergosterol content in M. purpureus. RNA high-throughput sequencing and Western blotting were used to analyze gene expression and histone modification levels in M. purpureus.ResultsWe found that co-culturing M. purpureus with SC-1 strain, resulted in a 45.1% increase in ergosterol content in M. purpureus. In addition, the transcription of ergosterol synthesis-related genes (ERGs) in M. purpureus was activated upon co-culture with SC-1 strain, accompanied by an increase in H3Kac levels. Interestingly, we further found that histone methyltransferase MpSet1 negatively regulated ergosterol synthesis in M. purpureus. Deletion of MpSET1 led to the activation of ERGs transcription and the increase of H3K4ac levels. Moreover, 45% of the upregulated differentially expressed genes (up_DEGs) in the wild-type (WT) co-cultured with SC-1 strain overlapped with the up_DEGs in the Δset1 strain, indicating that MpSet1 plays an important role in facilitating ergosterol synthesis in WT co-cultured with SC-1 strain.ConclusionThe study reveal that microbial co-cultivation can be used to facilitate ergosterol synthesis, and Set1 plays an important role in the ergosterol synthesis in fungi through affecting H3K4ac establishment.